Examining reading comprehension and critical thinking skills among fourth-grade elementary school students - Husnul Hotimah; Atep Sujana; Encep Supriatna; Iik Nurulpaik (CV. FOUNDAE, 2026)
Background: Reading comprehension and critical thinking are fundamental competencies that support students’ literacy development and learning across subjects. Nevertheless, many elementary school students still experience difficulties in interpreting texts and evaluating information critically. Aims: This study aims to examine the reading comprehension and critical thinking abilities of fourth-grade elementary school students in Indonesian language learning. Method: The study employed a descriptive quantitative design. Participants consisted of 37 fourth-grade students from a public elementary school in Serang City selected through purposive sampling. Data were collected using an essay-based test developed according to indicators of reading comprehension and critical thinking, including identifying problems, comparing arguments, proposing solutions, generating ideas, and expressing opinions. The instrument was validated through expert judgment to ensure content suitability. The collected data were analyzed using descriptive statistical techniques such as mean scores, percentages, and categorization of students’ ability levels. Results: The analysis revealed that students’ critical thinking skills generally fell into the moderate category with an average score of 60.14 out of 100. Students’ scores ranged from 30 to 80, with both the median and mode recorded at 65, indicating that most scores were concentrated around this value. In terms of category distribution, 21.62% of students were classified as low, 64.86% as moderate, and 13.51% as high. Conclusion: The findings suggest that although students have developed basic critical thinking abilities, their analytical reasoning and argumentation skills remain limited. Therefore, instructional strategies that encourage deeper reading, discussion, and reasoning activities are needed to strengthen students’ critical thinking development.